Moral Vision in The Stone Angel - Osachoff, Margaret Gail (Studies in Canadian Literature, 1979)
In Margaret Laurence’s The Stone Angel, the Manawaka town dump scene between Hagar and Lottie raises themes and issues that are integral to the understanding of Hagar and the moral vision of the novel.